Functional categorization of carbapenemase-mediated resistance by a combined genotyping and two-tiered Modified Hodge Test approach - Wong, Marcus H.; Li, Yi; Chan, Edward W.; Chen, Sheng (Frontiers in Microbiology, 2015)
The functional relationship between carbapenemase production and phenotypic resistance in Gram negative bacterial pathogens is often ill-defined. To address this issue, we developed a two-tiered Modified Hodge Test (MHT) approach for carbapenemase detection and typing, in which the use of Pseudomonas aeruginosa strain PAO1 and E. coli as indicator strains conferred two levels of sensitivities to carbapenemases. When applied alongside PCR genotyping tests for existence of known carbapenemase genes in 92 carbapenem resistant clinical isolates, this method is extremely useful in elucidating the relative role by which different enzymes contributed to the prevalent carbapenem-resistance phenotypes. With this study approach, we showed that the proportion of Pseudomonas aeruginosa and Acinetobacter baumannii strains whose carbapenem resistance phenotypes could at least be partially attributed to carbapenemase production were 34% and 89% respectively. Our data also facilitates detailed functional categorization of carbapenem resistance phenotypes on the basis of the nature and activities of detectable carbapenemase produced by the test organism. For example, six Acinetobacter baumannii isolates harbouring the blaOXA-51/23-like gene without expressing detectable enzymatic activities were identified, suggesting that other resistance mechanisms were involved. On the other hand, there were seven Pseudomonas aeruginosa strains which produced carbapenemase without harbouring known carbapenemase genes, inferring the existence of some hitherto unknown resistance determinants. Findings in this work therefore provide a comprehensive view on the cellular basis of carbapenem resistance phenotypes in major Gram negative bacterial species, paving the way for development of novel strategies to reverse the effects of the major resistance mechanisms concerned.